Mechanism of Micro-Crack Propagation in Semicrystalline Polymers - Stern, Theodor (Journal of Research Updates in Polymer Science, 2014)
The development and propagation of cracks is the principle reason for premature mechanical failure of polymeric materials. The well known and widely accepted fracture theories, namely the Griffith fracture theory and the Irwin model, both assume that fracture takes place through the presence of preexisting cracks in the polymer. These minor preexisting cracks, or micro-cracks, are practically present in most polymeric samples. The Griffith approach assumes that for any particular material, the fracture stress is controlled by the size of the flaws present in the structure. The control and minimization of micro-crack size during polymer processing requires an understanding of the inherent micro-crack propagation mechanism. The present research reveals a mechanism of internal stress-induced micro-crack propagation in semicrystalline polymers and describes the effect of the intricate crystalline morphological interactions on the extent and direction of intra-spherulite and inter-spherulite micro-crack propagation. In conclusion, a method for minimizing inter-spherulite micro-crack propagation is presented in this article.